Identification of miRNA, their targets and miPEPs in peanut (Arachis hypogaea L.). (December 2019) - Ram, Mousam Kumar; Mukherjee, Koel; Pandey, Dev Mani
Graphical abstract: Highlights: Seven new miRNAs were identified targeting 118 genes. miPEPs were also identified from pri-miRNA using ESTs. KEGG pathway analysis revealed involvement of miRNAs in 9 pathways. Abstract: MicroRNAs (miRNAs) are one of the major cytoplasmic tools employed by the eukaryotes for post-transcriptional gene regulation. These ˜21 nt small non-coding RNA molecules are highly conserved among species which forms a base for identification of new miRNAs. In this study, we used previously known mature miRNAs to search their homologs in Arachis hypogaea ESTs. A total of 50 non-protein coding sequences showing homology with no more than 3 mismatches were folded back to hairpin stem-loop structures using mfold. These predicted structures were passed through strict filtration criteria to obtain 18 miRNAs, all of which were other than those reported in miRBase. Out of 18 miRNAs, 7 were found to be new. These miRNAs belonged to miR156, miR166, miR167, miR319, miR398, miR399, miR482 and miR1507 family. These miRNAs were found to target a total of 118 genes in Arabidopsis . These targets included disease resistant proteins, auxin responsive proteins, squamosa promoter binding like proteins, co-transporter protein, transposable element genes, NAD(P) binding protein and topoisomerase II. KEGG pathway analysis showed potential involvement of these miRNAs in regulating different pathways. Apart from miRNA and their targets, microRNA encoded peptides (miPEPs) for 14 miRNAs were also identified. These findings can be used in the appropriate manipulation of miRNAs and corresponding miPEPs that will be helpful towards the peanut crop improvement.